A Comparative Study on Power MOSFET Reliability and Failure Modes - Bilir, Rahmet Aybuke; Altintas, Nihan; Bilir, Aydogan; Mese, Erkan; Tosunoglu, Zulal (IEEE, 2019)
In this study, based on the characteristic parameters of MOSFET's degradation, reliability of MOSFETs from different companies has been compared. Same type of MOSFETs are investigated. Acceleration test are designed and devices are degraded. According to degradation data, transfer characterization is investigated and failure modes of MOSFETs have been examined. This degradation data of values have been observed %10 variance which is degradation's sign.
Keywords: Degradation; Reliability; MOSFET; transfer characterisation; failure mode; Engineering